Can Fetal Echocardiographic Measurements of the Left Ventricular Outflow Tract Angle Detect Fetuses with Conotruncal Cardiac Anomalies? - Alona Raucher Sternfeld; Tal Betzer; Akiva Tamir; Yossi Mizrachi; Sagie Assa; Jacob Bar; Liat Gindes (Diagnostics, 2021)
Objectives: The angle between the inter-ventricular septum and the ascending aorta can be measured during a sonographic fetal survey while viewing the left ventricular outflow tract (LVOT angle). Our aim was to compare the LVOT angle between fetuses with and without conotruncal cardiac anomaliesrmations. Methods: In this prospective observational study, we compared the LVOT angle between normal fetuses, at different gestational age, and fetuses with cardiac malformations. Results: The study included 302 fetuses screened at gestational age of 12–39 weeks. The LVOT angle ranged from 127 to 163 degrees (mean 148.2), in 293 fetuses with normal hearts, and was not correlated with gestational age. The LVOT angle was significantly wider in fetuses with D-transposition of the great arteries (D-TGA, eight fetuses) and valvar aortic stenosis (AS, three fetuses), than in fetuses with normal hearts (164.8 ± 5.0 vs. 148.2 ± 5.4, respectively, p < 0.001). Conversely, the LVOT angle was significantly narrower in fetuses with complete atrioventricular canal defect (AVC, eight fetuses), than in fetuses with normal hearts (124.8 ± 2.4 vs. 148.2 ± 5.4, respectively, p < 0.001). On ROC analysis, an angle of 159.6 degrees or higher had a sensitivity of 100% and a specificity of 97.3% for the detection of TGA or AS, whereas an angle of 128.8 degrees or lower had a sensitivity of 100% and a specificity of 99.7% for the detection of AVC defect. Conclusions: The LVOT angle is constant during pregnancy, and differs significantly in fetuses with TGA/AS, and AVC, compared to fetuses with normal hearts (wider and narrower, respectively).